Literary text in the concept of culture - Djabbarova, Kizlarxan Abdulaxatovna (The Lingua Spectrum, 2026)
The article aims at researching the identification of the cultural components within a fictional text and analyzing the particular ways in which culture is represented in a text. Also, the article includes the analysis of: specifying the characteristic features of a fictional text; explaining how linguoculturemes are verbalized through the linguistic units at the lexical, phraseological, and parameological levels; providing the examples of mythologemes and religiously-marked linguistic units and demonstrate how authors utilize them in fictional texts; analyzing fictional texts in order to identify how concepts are utilized by the authors, to outline the characteristic features of literary concepts on the basis of the analysis. Additionally, the study explores the interrelation between language, culture, and artistic expression in fictional discourse. Moreover, special attention is paid to the role of nationally marked vocabulary, symbolic imagery, and culturally significant references that contribute to the formation of the author’s worldview within the text.